Hubungan Kepercayaan, Kualitas dan Kepuasan Terhadap Loyalitas Nasabah di KSPPS BMT Dinar Barokah Jumapolo Karanganyar - Leny Septyawati; Khabib Alia Akhmad; R. Taufiq Nur Muftiyanto (Jurnal Publikasi Ilmu Manajemen, 2024)
The banking sector is expanding quickly in this period of globalization and intensifying corporate competition. Building the loyalty of new customers and keeping hold of existing ones are two important components of successful banking. Thus, it is critical to conduct research on the variables that affect client loyalty if banks are to remain viable and expand. In this particular context, it has been acknowledged that customer pleasure, trust, and service quality play a significant role in fostering client loyaltyThe aim of this research is to determine and investigate how customer loyalty is impacted by quality, trust, and service satisfaction. Customers of KSPPS BMT Dinar Barokah Jumapolo who have completed service transactions at the cooperative made up the study's population. Purposive sampling is is the sampling technique applied in this research.